Early Warning Score (EWS) And Shock Index (SI) Patients With Physical Restraints (Hand Fixation) In Patients Receiving Intensive Care - Heru Suwardianto; Sandy Kurniajati (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: Patients with critical conditions may experience agitation and also require immobilization. The patient needs a fixation on the hand (physical restraint) so that medical and nursing interventions can be carried out. Methods: The research method uses a quasi-experimental posttest design. Patients who received physical fixation intervention or physical restraint in an inpatient room at Baptist Hospital Kediri comprised the population.The study was conducted from June to July 2022. The sample size of the study was 57 patients, using a purposive sampling technique with inclusion criteria, namely total care patients, patients receiving restraints and having Richmond Agitation Sedation Scale (RASS) values > +1, and patient exclusion, i.e., patients receiving treatment less than twice a day at 24 o'clock. The independent variables are EWS and SI, and the dependent variables are. Statistical test using Mann Whitney with < 0.05. Results: The results showed that the Early Warning Score (EWS) variable obtained a value of Z = -1.787 with a p value of 0.238, which means that there was no difference in the EWS value in the control group and the experimental group. The results of the study on the EWS variable obtained a value of Z = -181 with a p value of 0.074, which means there is no difference in the EWS value in the control group and the experimental group. Conclusion:  EWS and SI did not have a significant difference in the two groups, it is necessary to conduct a study on the physical condition or physical and psychological symptoms of the restraint measures given.